2016
DOI: 10.1021/acs.joc.6b00341
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Aza-Michael Addition of Aromatic Amines or Aromatic Aza-Heterocycles to α,β-Unsaturated Olefins

Abstract: A highly efficient and mild Cu-catalyzed conjugate addition reaction of aromatic amines and aromatic aza-heterocycles to α,β-unsaturated olefins is described. The transformation is promoted by 3-7 mol % of a Cu complex generated in situ from a mixture of inexpensive CuCl, a readily available phosphine or imidazolium salt, and KOt-Bu at ambient temperature. A wide range of β-amino sulfone, β-amino nitrile, and β-amino carbonyl compounds is efficiently and selectively synthesized in high yields (62-99%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 82 publications
0
38
2
Order By: Relevance
“…Other attempts also proved unsuccessful, resulting either in the absence of the product or low yields in a difficult to separate mixture. 2,3-Dihydro-1H-pyrrolizin-1-one can be readily prepared from pyrrole and methyl acrylate (Jefford et al 1994;Kim et al 2016). Dehydrogenation via a selenoxide resulted in a good yield of 1H-pyrrolizin-1-one, however, introduction of the methylene group via Wittig-, Petasis-or methyl lithium addition approaches did not result in a clean product.…”
Section: Gc/ms Analyses Of Androconia To Test This Hypothesis O Onmentioning
confidence: 99%
“…Other attempts also proved unsuccessful, resulting either in the absence of the product or low yields in a difficult to separate mixture. 2,3-Dihydro-1H-pyrrolizin-1-one can be readily prepared from pyrrole and methyl acrylate (Jefford et al 1994;Kim et al 2016). Dehydrogenation via a selenoxide resulted in a good yield of 1H-pyrrolizin-1-one, however, introduction of the methylene group via Wittig-, Petasis-or methyl lithium addition approaches did not result in a clean product.…”
Section: Gc/ms Analyses Of Androconia To Test This Hypothesis O Onmentioning
confidence: 99%
“…We commenced our studies with 4-nitrostyrene (1 a) and 4-methoxyaniline (2 a) as the model substrates, as shown in Table 1. Guided by our previous studies on aza-Michael reactions, [12] we initially attempted the addition of amine 2 a to 1 a in the presence of IPrCuCl and KOt-Bu in toluene at ambient temperature. However, the reaction did not proceed (< 2% of 3 aa).…”
Section: Resultsmentioning
confidence: 99%
“…[11] In our previous studies, we demonstrated an aza-Michael addition of (hetero)aryl amines to a,bunsaturated carbonyls catalyzed by a copper complex generated in situ from the reaction of a phosphine or an imidazolinium salt with CuCl and KOt-Bu under mild conditions. [12] As a continuation of our studies on the synthesis of amine compounds from alkenes using a copper catalyst, we report herein an efficient and mild Cu-catalyzed intermolecular anti-Markovnikov hydroamination of vinylarenes with arylamines or heterocycles (Scheme 1c). A readily prepared NHC-CuCl species in the presence of KOt-Bu and MeOH promoted the addition of the amine to various monoand 1,2-disubstituted vinylarenes, providing various novel arylamine and azole products in good to excellent yields.…”
Section: Introductionmentioning
confidence: 97%
“…However, the use of acids and alkalis has brought challenges to the environment. In order to avoid such problems, various transition-metal catalysts have been developed and used to efficiently catalyze the Michael addition to synthesize β-amino acid esters [12][13][14][15][16][17]. Although desired results were obtained, the use of metal catalysts and expensive ligands are still shortcomings for the practical utility.…”
Section: Introductionmentioning
confidence: 99%